PENDIDIKAN KESEHATAN TENTANG PERUBAHAN FISIK DAN PSIKOLOGIS PADA MASA KLIMAKTERIUM - Munisah, Munisah; Handajani, Diani Octaviyanti; Sukarsih, Rahmawati Ika; Yuliati, Luluk (Indonesian Journal of Community Dedication in Health (IJCDH), 2023)
The period of normal female anatomy and physiology development is indicated through six stages: prepuberty, puberty, reproductive period, climacteric and menopause, and senium. The reproductive period can be said to be the most important period in a woman's life which can last approximately 33 years. Towards the end of this reproductive period, it is called the climacteric period which is the transition period from the reproductive period to the senium period. In general, the symptoms caused by menopause are irregular menstruation, and hot flushes (hot flashes, emotional changes). In addition to these symptoms, menopausal women will experience a tendency to increase the amount of bone fragility (osteoporosis) and can be more susceptible to several diseases, such as heart disease. and blood vessels. This community service aims to increase women's knowledge about the physical and psychological changes that occur so that women are ready to face the climacteric period. This community service was carried out in the Pangajian Al-Hidayah DPP Gresik Regency group. By carrying out health education about the changes that occur during the climacteric period, these women finally understand the condition of their bodies, so that they can deal with any discomfort and anxiety about their body's condition does not occur.